Enhanced Bioavailability of Valsartan through Mucoadhesive Pellets Fabricated via Fluidized Bed Processor: A Novel Drug Delivery Approach - Baste, Nayana; Gangurde, Hemant; Nemade, Charulata; Shahare, Hitesh; Bihani, Manisha (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Novel delivery strategies are being explored since low bioavailability presents a challenge for medications like valsartan. Mucoadhesive drug delivery systems present a viable alternative by enhancing drug absorption and retention. Aim This study aimed to develop mucoadhesive drug delivery systems to enhance the bioavailability of valsartan, leveraging a novel mucoadhesive polymer isolated from Samaneasaman seeds. Materials and Methods The study involved formulating oral mucoadhesive pellets by layering valsartan on starch pellets, followed by coatings of release-retardant polymer HPMC K15M and the novel Samanea saman gum. Optimization was achieved through response surface methodology, with assessments including mucoadhesive strength, drug release kinetics, compatibility studies, and pharmacokinetics evaluation. Results and Discussion The optimized formulation, featuring 10% w/w HPMC K15M and 40% w/w Samanea saman gum coating, exhibited robust mucoadhesive strength and sustained drug release for 14 hr. Increasing Samanea saman gum concentration enhanced mucoadhesive strength and drug release retardation. Compatibility assessments confirmed the suitability of excipients, while microscopy and radiography revealed pellet integrity. Conclusion The developed mucoadhesive drug delivery system effectively enhanced the bioavailability of valsartan, as evidenced by in vitro dissolution studies and in vivo pharmacokinetic studies in rats. This comprehensive approach offers a promising strategy for improving the therapeutic efficacy of valsartan through enhanced mucoadhesion and sustained release.
Keywords: Mucoadhesive drug delivery systems; Valsartan bioavailability; Samaneasaman gum; Sustained drug release; Pharmacokinetic studies